Microbial ecotoxicology - Cravo-Laureau, Cristiana; Cagnon, Christine; Lauga, Béatrice; Duran, Robert (Springer, 2017)
This book is a treatise on microbial ecotoxicology, discussing the effect of pollutants on microbial ecosystems and the role of microorganisms in ecosystems services. Emphasizing the microbial responses to pollution at different biological levels, it focuses on metabolic pathways, genetic adaptation and response at the whole-microbial community level. It also addresses the ecological indicators of ecosystem recovery, as well as microbial biomarkers and biosensors as tools for microbial ecotoxicology.
8.2 How Do Contaminants Change Structural Components of Microbial Communities?
Keywords: Microbial toxins.; Environmental toxicology.; elektronické knihy; electronic books